Databank of genomic sequences of pathogenic microorganisms and its role in the implementation of epidemiological surveillance - T. A. Semenenko; V. G. Akimkin; T. V. Solomay (Кардиоваскулярная терапия и профилактика)
Despite the fact that databanks of genomic sequences have clear information links with biological samples, they are an independent intellectual resource in demand among many researchers. To deposit information obtained in the course of molecular genetic studies in Russia, the Virus Genome Aggregator of Russia (VGARus) databank was created.Aim. To evaluate data on the variability of genetic sequences of the Epstein-Barr virus (EBV), obtained as a result of Russian studies, and the possibility of their integration into the VGARus database forsubsequent use in epidemiological surveillance.Material and methods. A search for publications was carried out in the PubMed, eLibrary, Cyberleninka databases. In total, the study included 32 papers of Russian and external authors that meet the stated aim. Results. The number of studies containing data on the EBV genetic sequences in the Russian Federation is extremely small. The information presented in publications indicates geographical differences in the ratio of two EBV genotypes, the presence of a special LMP1 TatK gene variant in the Tatars of the Volga region, the difference between Russian EBV samples in the gene encoding the gp350 from those from other world regions. At the same time, information on the genomic sequences obtained in the studies was not deposited in the Russian gene bank in any case.Conclusion. Expanding the potential of the Russian VGARus platform by including information on the genomic sequences of all pathogenic microorganisms circulating in the Russian Federation will require largescale work that takes into account technical features, biological and information security requirements.